Sickle cell cerebrovascular reactivity to a CO2 stimulus: Too little, too slow - Forté, Stéphanie; Sobczyk, Olivia; Poublanc, Julien; Duffin, James; Hare, Gregory M. T.; Fisher, Joseph Arnold; Mikulis, David; Kuo, Kevin H. M. (Frontiers in Physiology, 2022)
Background: Despite increased cerebral blood flow (CBF), cerebral infarcts occur in patients with sickle cell disease (SCD). This suggests increased CBF does not meet metabolic demand possibly due to compromised cerebral vasodilatory response. Hypothesis: In adult SCD patients, cerebrovascular reactivity (CVR) and speed of vasodilatory response (tau) to a standardized vasodilatory stimulus, are reduced compared to normal subjects. Methods: Functional brain imaging performed as part of routine care in adult SCD patients without large vessel cerebral vasculopathy was reviewed retrospectively. CVR was calculated as the change in CBF measured as the blood-oxygenation-level-dependent (BOLD)-magnetic resonance imaging signal, in response to a standard vasoactive stimulus of carbon dioxide (CO2). The tau corresponding to the best fit between the convolved end-tidal partial pressures of CO2 and BOLD signal was defined as the speed of vascular response. CVR and tau were normalized using a previously generated atlas of 42 healthy controls. Results: Fifteen patients were included. CVR was reduced in grey and white matter (mean Z-score for CVR -0.5 [-1.8 to 0.3] and -0.6 [-2.3 to 0.7], respectively). Tau Z-scores were lengthened in grey and white matter (+0.9 [-0.5 to 3.3] and +0.8 [-0.7 to 2.7], respectively). Hematocrit was the only significant independent predictor of CVR on multivariable regression. Conclusions: Both measures of cerebrovascular health (CVR and tau) in SCD patients were attenuated compared to normal controls. These findings show that CVR represents a promising tool to assess disease state, stroke risk, and therapeutic efficacy of treatments in SCD and merits further investigation.